The use of Dimia for the treatment of premenstrual syndrome in adolescent girls - Elena V Sibirskaya; Gulnoza M Turgunova (IP Berlin A.V., 2019)
Today, premenstrual syndrome (PMS) remains one of the relevant issues of adolescent gynecology. The difficulty in treatment of PMS in adolescent girls is associated with a large number of factors. The combination of hormonal, neuro-vegetative, metabolic, mental and emotional deviations requires a comprehensive and more differentiated approach to the treatment of this disease. Aim. Assessment of clinical efficacy and safety of using drospirenone 3 mg and ethinylestradiol 20 µg combination for the treatment of PMS in adolescent girls aged 14-18. Outcomes and methods. The study included female 50 patients who met the criteria: age of 14 to 18 years, no severe extragenital pathology, the menstrual cycle duration within 6 months - 25-32±2 days. Based on examination data, all patients were prescribed a drug containing 3 mg of drospirenone and 20 μg of ethinylestradiol. The duration of therapy was 6 months. Results. Under the drug therapy, a significant decrease in the intensity of PMS manifestations occurred. Conclusions. The use of drospirenone 3 mg and ethinylestradiol 20 µg combination for 3 months in patients with PMS has a beneficial effect on the autonomic nervous system, significantly reduces the rate of pain before and during menstruation, helps to decrease the number and intensity of menstrual flow and ultimately significantly improves the quality of patient life.